2013
DOI: 10.1186/1824-7288-39-25
|View full text |Cite
|
Sign up to set email alerts
|

Serum hepcidin: indication of its role as an “acute phase” marker in febrile children

Abstract: BackgroundHepcidin is classified as a type II acute phase protein; its production is a component of the innate immune response to infections.ObjectiveTo evaluate the alterations of serum hepcidin in children during and following an acute febrile infection.Materials and methods22 children with fever of acute onset (< 6 hours) admitted to the 2nd Department of Pediatrics-University of Athens. Based on clinical and laboratory findings our sample formed two groups: the viral infection group (13 children) and the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 27 publications
(24 reference statements)
2
18
0
Order By: Relevance
“…The majority (5/7; 71%) of studies that evaluated ESR, a marker for inflammation found it to be a specific marker in differentiating between bacterial and non-bacterial infections [ 24 , 29 , 30 , 36 , 37 , 41 , 49 ]. Patients with bacterial infections had a higher ESR than patients with viral infections [ 30 ]; [ 49 ]; [ 29 , 36 , 37 ]. Two studies reported the diagnostic performance characteristics of ESR, which ranged from 77.4%-85% sensitivity and 78.3%-90% specificity to identify bacterial infections [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority (5/7; 71%) of studies that evaluated ESR, a marker for inflammation found it to be a specific marker in differentiating between bacterial and non-bacterial infections [ 24 , 29 , 30 , 36 , 37 , 41 , 49 ]. Patients with bacterial infections had a higher ESR than patients with viral infections [ 30 ]; [ 49 ]; [ 29 , 36 , 37 ]. Two studies reported the diagnostic performance characteristics of ESR, which ranged from 77.4%-85% sensitivity and 78.3%-90% specificity to identify bacterial infections [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the studies that evaluated inorganic molecules, chloride in CSF [ 21 , 28 ] and serum iron [ 36 ] reported statistically significant differences in the levels observed in bacterial versus non-bacterial infection patients. Chloride concentrations in CSF were compared in two meningitis studies, but the sensitivities differed greatly.…”
Section: Resultsmentioning
confidence: 99%
“…Park et al [15] found that patients showed high-level hepcidin in the acute infection stage after gastric resection, colon-liver resection, liver resection and operation for diffuse peritonitis. Kossiva et al [16] found in their clinical study that hepcidin was significantly increased in the acute phase of pediatric infectious fever, and there was no significant difference between the virus group and bacterial group.…”
Section: Discussionmentioning
confidence: 96%
“…[51] IL-1 in association with the acute phase response also decreases plasma iron content and it is challenging to speculate that the sequestration of less deformable erythrocytes by endothelial cells in the spleen also plays a causative role in shortened halflife of erythrocytes thus, resulting in anemia. [52] Alternatively, a rise in both WBC and platelet counts might be due to the stimulation of immune system against the invading pathogenic microorganism and it is evident by the influx of inflammatory mononuclear cells in the joints of arthritic rats. [53,54] In the present experimental study, the herbal formulationtreated groups had considerably increased level of Hb and RBC, while the level of WBC and platelets was significantly reduced in contrast to arthritic control group but comparable to normal control group [ Table 6].…”
Section: Discussionmentioning
confidence: 99%